10-Membered Azaenediyne Fused to a Benzothiophene through the Nicholas Macrocyclization: Synthesis and DNA Cleavage Ability - Danilkina, Natalia A.; Rumyantsev, Andrey M.; Lyapunova, Anna L.; D’yachenko, Alexander S.; Khlebnikov, Alexander F.; Balova, Irina A. (Synlett, 2019)
The Nicholas-type macrocyclization through NH-tosyl functional group has been found to be an efficient technique for the synthesis of a 10-membered azaenediyne system annulated with a benzothiophene. To compare the activity of azaenediyne synthesized with similar oxa- and carbocyclic enediynes the Bergman cyclization activation energies and the ability of enediynes to cleave DNA (pBR322 plasmid) were investigated. The order of reactivity predicted by DFT calculations (N-enediyne < C-enediyne < O-enediyne) was confirmed by DSC analysis data. Surprisingly azaenediyne was found to be more active in the DNA cleavage assay than the C-analogue.
Keywords: Nicholas reaction; Bergman cyclization; iodocyclization; enediyne; alkyne; benzothiophene; pBR322 plasmid